Enhanced production of iturin A by strengthening fatty acid synthesis modules in Bacillus amyloliquefaciens - Gao, Lin; She, Menglin; Shi, Jiao; Cai, Dongbo; Wang, Dong; Xiong, Min; Shen, Guoming; Gao, Jiaming; Zhang, Min; Yang, Zhifan; Chen, Shouwen (Frontiers in Bioengineering and Biotechnology, 2022)
Iturin A is a biosurfactant with various applications, and low synthesis capability limits its production and application development. Fatty acids play as the critical role in cellular metabolism and target products syntheses, and the relationship between fatty acids supplies and iturin A synthesis is unclear. In this study, we attempted to increase iturin A production via strengthening fatty acids synthesis pathways in Bacillus amyloliquefaciens. Firstly, acetyl-CoA carboxylase AccAD and ACP S-malonyltransferase FabD were overexpressed via promoter replacement, and iturin A yield was increased to 1.36 g/L by 2.78-fold in resultant strain HZ-ADF1. Then, soluble acyl ACP thioesterase derived from Escherichia coli owned the best performance for iturin A synthesis, compared to those from B. amyloliquefaciens and Corynebacterium glutamicum, and introduction of which in HZ-ADF1 further led to a 57.35% increase of iturin A yield, reached 2.14 g/L. Finally, long chain fatty acid-CoA ligase LcfA was over-expressed in HZ-ADFT to attain final strain HZ-ADFTL2, and iturin A yield reached 2.96 g/L, increased by 6.59-fold, and the contents of fatty acids were enhanced significantly in HZ-ADFTL2, compared to original strain HZ-12. Taken together, our results implied that strengthening fatty acids supplies were an efficient approach for iturin A production, and this research provided a promising strain for industrial production of iturin A.